Local-global design: entrepreneurial ecosystem approach for digital gaming industry. (27th December 2021) - Xu, Zimu; Sukumar, Arun; Jafari-Sadeghi, Vahid; Li, Fujia; Tomlins, Richard
The notion of the entrepreneurial ecosystem has gained considerable traction in recent years. Ecosystem approach is considered as a useful mechanism in supporting entrepreneurial activities, regional economic development and addressing sustainable development goals. This paper explores the entrepreneurial ecosystem concept and its applicability in the context of the gaming industry. By looking at Brazilian gaming industry, this paper explores the variations in entrepreneurial ecosystems that are favourable for technology-dependent industries such as gaming, especially in developing economies. The paper follows a qualitative approach using document analysis and attempts to develop a local-global (LOGO) framework that examines current evidence in the digital gaming ecosystem. Findings of this research suggest that, depending on the ecosystem maturity, components of an ecosystem play either a dominant global role or a weaker local role in supporting entrepreneurial initiatives. When serving a global market, ecosystems change and mature, so do the roles played by their components. The proposed conceptual framework re-visits the entrepreneurial ecosystem approach and its role in the development of the gaming industry. The paper contributes by extending the current theory pertaining to ecosystem approaches and suggests practical routes for ecosystem components to work effectively in scaling from a local to a global market.